2018
DOI: 10.3390/su10040947
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk of Bankruptcy of Tomato Processing Companies Operating in the Inter-Regional Interprofessional Organization “OI Pomodoro da Industria Nord Italia”

Abstract: The tomato sector is a major area of agricultural activity in Italy; tomato production and processing characterize different Italian regions; in particular, there are two production districts, one in southern Italy and one in northern Italy, in the Po Valley. In recent years, processing firms have encountered increasing difficulties, due both to an increase in raw material costs and market difficulties. Tomato processing firms are often characterized by significant investment in fixed assets and working capita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Prediction of financial distress or bankruptcy risks by employing the appropriate model with high accuracy has become an important research issue in the area of business analytics [1,2,66]. In this study, we have suggested a new kind of hybrid SVM and GA model, termed GOSVM, in order to improve the performance of the typical SVM algorithm for financial distress prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of financial distress or bankruptcy risks by employing the appropriate model with high accuracy has become an important research issue in the area of business analytics [1,2,66]. In this study, we have suggested a new kind of hybrid SVM and GA model, termed GOSVM, in order to improve the performance of the typical SVM algorithm for financial distress prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Every firm is part of a network of relations, such as; labor relations, supplier relations, sales relations, customer relations, financial institutions relations, tax payments, social relations and many more. Therefore, any financial trouble within a firm will directly impact its associated socio-economic system and subsequently sustainability in the long-run [4,5]. Li et al [6] states that high financial risk has serious implications for a firm's financial sustainability, while studies such as [7,8] point out that financial distress threatens the corporate financial health.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the establishment of an early warning mechanism for financial distress can improve a firm's financial sustainability. Consequently, recent studies [4,9] have employed different measures of financial distress to gauge the financial sustainability of firms.…”
Section: Introductionmentioning
confidence: 99%
“…Tomatoes are vulnerable to postharvest losses due to their perishable nature [8]. In recent years, tomato processing firms have encountered increasing difficulties, due both to an increase in raw material costs and market difficulties [9].…”
Section: Introductionmentioning
confidence: 99%